Direito de propriedade urbano brasileiro e bem-estar social - Zazyki, Marco Aurélio Denis (2017)
The master thesis has as object of study the analysis of urban property rights and welfare in light of Brazilian Law/88. It is analyzed how the state proposes the regulation of property rights in order to promote social welfare. The methodology is characterized by an exploratory study from a literature review related to Brazilian urbanization process, the approach of property rights: from the point of view of Douglass North, Ha- Joon Chang and how the Brazilian law/88 it addresses the issue. It was analyzed the relationship between property rights and well-being with the criticism of utilitarianism in the view of Amartya Sen, according to the theory of training to assess welfare. The ideas of North, Chang and Sen proved to be appropriate in the discussion of the topic, revealing limitations on the applicability of property rights and the utilitarian view of well-being, present in the regulation of these.